The true nature of reality - Al'Mahdi, Muhammad, Dr.; Saba Islamic Media (Kuala Lumpur : Saba Islamic Media, 2004)
A broad reaching explanation of Allah's grand cosmic plan which includes a scientific view of His physical universe, combined with our first objective glimpse of the spiritual world from modern physics. Together these give us an unprecedented understanding of the exquisite magnificence of being a Muslim in today's world.
Host: Dr. Muhammad Al'Mahdi
VCD format
Keywords: Science and Islam